Personal dietary characteristics, destination image and Behavioural intentions: food tourism in Chengdu - Qin Xue Wang; Juliana Langgat; Marry Tracy Pawan (UMS, 2022)
Food has become an indispensable part of the tourism industry, and there are inextricable links between food and tourism. Tourist food destination is widely promoted on various websites and has become the destination’s most crucial cultural expression. Personality dietary characteristics, destination image, and behavioural attention can influence food tourism’s positive development at a destination. Chengdu, China, was chosen as a case setting to explore the effect of food tourism in China. A quantitative research approach and a selfadministered questionnaire were adopted in this study. One hundred and sixty-nine respondents participated in this study, and the data were analyzed using Smart-PLS. Personal dietary characteristics were found to have an indirect effect on tourist behaviour intentions and destination image. This study will help the industry formulate corresponding management strategies for multiple influencing factors of food tourist behaviour and enhance the competitiveness of destinations.